Unilateral Cervical Lymphadenopathy due to Cladosporium oxysporum: A Case Report and Review of the Literature. (25th October 2017) - Jayasinghe, R. D.; Abeysinghe, W. A. M. U. L.; Jayasekara, P. I.; Mohomed, Y. S.; Siriwardena, B. S. M. S.
Abstract : Phaeohyphomycosis is a fungal infection caused by Dermatiacae group of fungi, by Cladosporium spp. The term phaeohyphomycosis was introduced by Ajello et al. in 1974 to designate infections by brown pigmented filamentous fungi. Cladosporium oxysporum is a very rare etiological agent in humans. Phaeohyphomycosis of the cervical lymph node in an immunocompetent individual is a very rare clinical entity. To the best of our knowledge we report the first case of phaeohyphomycosis caused by Cladosporium oxysporum in the absence of other systemic manifestations in a 16-year-old male.